STRATEGI CUSTOMER RELATIONSHIP MANAGEMENT DAN EVALUASI SOFTWARE USABILITY MEASUREMENT INVENTORY DALAM PEMBUATAN WEB PERUSAHAAN (STUDI KASUS: SEKOLAH MUSIK GEMA SUARA BOGOR) - Neyman, Shelvie Nidya; Wijaya, Yohanes Aditya; Rachmaniah, Meuthia (Prosiding SeNAIK, 2013)
Company website is a marketing tools wich has function for spreading information about company products to attract new customers and also for keeping the relationship with the customer to get the their loyalty. This reseach purpose is applying a method in the making of company website, so this application can produce a company website wich function is for not only spreading company information but also making relationship with customer. Customer Relationship Management (CRM) is developing because of the requirement to maintain customer relationship. The using of CRM strategy in making company website can realize websites function as a marketing tools which attracting new customer and keeping old customer. This research is conducted using three main steps of CRM strategy that are customer portofolio analysis, resources development, and website development. After all those steps, website evaluation is carried out using Software Usability Measurement Inventory (SUMI) questionnaire to evaluate user satisfaction. In this paper, application of CRM strategy in developing company education website was equipped with facilities that give value for the customers, therefore the company website could attract new customers, and also increase old customer loyalty. Website evaluation using SUMI questionnaire in SMGS website shows that the users of SGMS website are satisfied. It is shown by each categories score dan global score that are higher than average standard scores. Efficiency score is 90, affect score is 80, helpfullness score is 80, learnability score is 90, control score is 65 dan global score is 83 compare to average standard score is 50.